Synthesis and Properties of BODIPY Appended Tetraphenylethylene Scaffolds as Photoactive Arrays - Senge, Mathias; Khurana, Bhavya; Grover, Nitika; Twamley, Brendan; Emandi, Ganapathi; Sample, Harry C. (My University, 2021)
Tetraphenylethylene (TPE) and its derivatives exhibit excellent aggregation-induced emission (AIE) properties. The TPE unit is easily accessible, and many functional groups can be introduced in a facile manner to yield effective luminescent materials in both solution and the solid-state. It is because of this, several TPE-based compounds have been developed and applied in many areas, such as OLEDs and chemical sensors. Boron dipyrromethenes (BODIPYs) are a class of pyrrolic fluorophore of great interest with myriad application in both material science and biomedical applications. Through the combination of Pd-catalyzed cross-coupling reactions and traditional dipyrromethene chemistry, we present the syntheses of novel tetra-BODIPY-appended TPE derivatives with different distances between the TPE and BODIPY cores. The TPE-BODIPY arrays 6 and 9 show vastly differing AIE properties in THF/H2O systems, with 9 exhibiting dual-AIE, along with both conjugates being found to produce singlet oxygen (1O2). We presume the synthesized BODIPY-appended TPE scaffolds to be utilized for potential applications in the fields of light-emitting systems and theranostics.
Keywords: BODIPY; Tetraphenylethylene (TPE); aggregation-induced emission